2010 International Students and Young Scientists Workshop "Photonics and Microsystems" 2010
DOI: 10.1109/stysw.2010.5714165
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene based materials for ultra-low-k application

Abstract: Fullerene-based materials are considered to be a candidate for ultra-low-k material applications. We have incorporated fullerene C60 into a siloxane material by means of the sol-gel method. Thickness of obtained film was investigated by atomic force microscope, dielectric constant was measured by the capacitance-voltage characterization (CV). Interactions between the components within the films were investigated by using X-ray photoelectron spectroscopy and near edge X-ray absorption fine structure spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Firstly, we shortly reflect the hysteresis inside the CV measurements which we observed in all of our investigated siloxane-based films [10][11][12]15]. Figure 2 Obviously, in agreement with our previous reports [11,12], the hysteresis of the pure APTMS film is much higher than in the CuPc/PCBM/POSS incorporated film.…”
Section: Hysteresis Inside CV Characterizationsupporting
confidence: 86%
“…Firstly, we shortly reflect the hysteresis inside the CV measurements which we observed in all of our investigated siloxane-based films [10][11][12]15]. Figure 2 Obviously, in agreement with our previous reports [11,12], the hysteresis of the pure APTMS film is much higher than in the CuPc/PCBM/POSS incorporated film.…”
Section: Hysteresis Inside CV Characterizationsupporting
confidence: 86%
“…Satellites are visible on the higher binding energy side (2)(3)(4)(5), which are characteristic for PCBM [14]. The two [15].…”
Section: Resultsmentioning
confidence: 99%
“…Fullerenes are also extensively investigated for ultra lowk investigations because of ability to form porous frameworks [3][4][5]. Replacing C 60 with the better soluble derivative PCBM showed positive effects on the reduction of the dielectric constant [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that fullerenes are considered as promising candidates for design of low k dielectrics [54][55][56][57]. On the other hand the studies of dielectric properties of carbon nanotubes indicated the potential of these structures to be the basis for high k dielectrics.…”
Section: Dielectric Constantmentioning
confidence: 99%